Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Delfiani, Silvi; Febriyanti, Herlinda Fitri (Politeknik Raflesia Press, 2024)
This research aims to examine the effect of insider ownership, institutional ownership, foreign ownership, public ownership, and firm size on a company’s performance in non-financial companies. The populations of this research are all of the non-financial companies listed in the Indonesia Stock Exchange (IDX). The sampling technique use the purposive sampling method, in order this study obtained 64 sample companies. The technique of analyzing data used multiple regression. This study used a statistical t-test with α level of 5% by SPSS 16 to test the hypothesis. The results showed that insider ownership has a positive and insignificant effect on the company’s performance, institutional ownership has a negative and insignificant effect on the company’s performance, foreign ownership has a negative and insignificant effect on the company’s performance, public ownership has a negative and insignificant effect on company’s performance and firm size has a positive and significant effect on company’s performance of non-financial companies.